An Improved Method to Detect Shoreline Changes inSmall-Scale Beaches Using Google Earth Pro - Warnasuriyaa, T.W.S.; Kumara, M.P.; Gunasekara, S.S.; Gunaalan, K.; Jayathilaka, R.M.R.M. (Taylor & Francis Group, 2020)
Shoreline change studies in small-scale beaches require high-resolution satellite images. In this regard, high-resolution satel-lite images from Google Earth (GE) would be an alternativesource however novel studies are needed to verify the effective-ness and the efficiency of applying those images for shorelinechange detection in small-scale beaches. Addressing this gap,the current study attempts to develop a new method.Accuracies of delineated shorelines under different scenarioswere used to develop relationships with digitizing methods andused eye-altitude to estimate the most effective, efficient andproductive method. This was done using Digital ShorelineAnalysis System (DSAS) in ArcGIS software. It was found that theeye-altitude influences on digitizing accuracy and it could beimproved when increasing the zoom level of the image which isunder investigation. Maximum zoom level (50m) used in thisstudy showed the highest accuracy in shoreline digitizing whilethe most productive eye-altitude for shoreline delineation wasfound as 300m. The current study identified that GE coupledwith DSAS tool in ArcGIS software can be used as an effectiveand efficient method for small-scale shoreline change analysisand it is suggested that this methodology could be adopted forother similar studies
Keywords: DSAS; GIS; Google EarthPro; Remote sensing; Small-scale beach